Resilience of family caregivers of people with dementia in South Korea: protocol for a scoping review - Hyun-Ju Seo; Min-Jung Choi; Song-I Park; Jeong-hwan Park (BMJ Open)
Introduction The prevalence of dementia among the elderly population in South Korea was 9.94% in 2017, and the number of people living with dementia is estimated to increase up to one million by 2024. Considering that approximately 55%–85% of people with dementia are taken care of by family members in South Korea, the phenomenon of resilience for family caregivers with patients with dementia should be understood within a Korean cultural context. The purpose of this paper is to describe the protocol of a scoping review addressing the resilience of family caregivers for Koreans with dementia.Methods and analysis Arksey and O'Malley’s scoping review framework and Joanna Briggs Institute’s manual for scoping reviews will guide the review methods. Multiple databases, including Ovid-MEDLINE, Ovid-EMBASE, PsycINFO, Cumulative Index for Nursing and Allied Health Literature and Korean databases will be identified using controlled vocabulary and text words. Two review authors will independently screen and select studies based on predefined eligible criteria. The extracted data will undergo descriptive analysis of the contextual data and a quantitative analysis using the appropriate descriptive statistics.Ethics and dissemination Because the scoping review methodology consists of reviewing and collecting data from the published literature, this study does not require ethics approval. This scoping review will serve to highlight existing gaps within the literature to guide further research and to develop future strategies to measure and improve the resilience of family caregivers for patients with dementia in South Korea.